Adesão de células sanguineas em raízes biomodificadas de pacientes fumantes - Magri, Lais Valencise [UNESP]; Cavassim, Rodrigo [UNESP]; Sampaio, Jose Eduardo Cezar [UNESP] (My University, 2011)
The periodontal treatment begins with scaling and root planning and patient motivation, aiming at an increase in oral health. Scaling and root planning produce smear layer which impairs periodontal regeneration. Chemical substances are used to remove this layer exposing a sound root surface and collagens fibers. Some substances are proposed to it: tetracycline, EDTA, citric acid and lasers. Several researches were conducted in order to determine the best way to apply those substances. These researches determined the adequate concentration, period and method of application to promote root demineralization. The aim of this study was to evaluate blood cell adhesion to collagen of demineralized dental surfaces in association of plasma rich platelet application. 24% EDTA, 25% citric acid (pH 1.5) and distilled water (control) were used in the teeth of the smoking patients. After the samples were photographed in a scanning electron microscope, non-parametrical analysis was performed to evaluate the formation and interlacing of network fibrinolytic and adhesion of blood cells to the root surface. It can be concluded that the use of EDTA and citric acid did not affect the adhesion of blood cells. The application of PRP before the deposition of tissue blood seems to have influenced the adhesion of cells to the root surface. The use of EDTA and citric acid in combination to PRP favored the adhesion of blood cells. EDTA and citric acid removed smear layer and exposed dentinal tubules; but were not effective in the exposure of collagen fibers.

O tratamento periodontal inicia-se com raspagem e aplainamento radicular e a motivação do paciente, visando melhoria na higienização e na saúde bucal do indivíduo. A raspagem e o aplainamento radicular formam smear layer, dificultando a reparação periodontal. Substâncias químicas são utilizadas para remoção desta camada, promovendo a exposição de superfície radicular sadia e fibras colágenas. Vários agentes condicionantes são propostos: tetraciclina, EDTA, ácido cítrico e laser. Para determinar a melhor maneira de utilizar essas substâncias, foram realizados estudos que determinaram quais as concentrações, tempos e modos de aplicação em relação à biomodificação radicular. O objetivo deste estudo foi avaliar a adesão das células sanguíneas ao colágeno da superfície dental, exposto por condicionadores associados ao plasma rico em plaquetas. Assim, utilizou-se o EDTA 24%, o ácido cítrico 25% (pH 1,5) e a água destilada (controle) em dentes de pacientes fumantes. Após, as amostras foram fotografadas em microscópio eletrônico de varredura, realizada análise estatística não paramétrica quanto ao grau de formação e entrelaçamento da rede fibrinolítica e a adesão das células sanguíneas à superfície radicular. Pôde-se concluir: a utilização de EDTA e ácido cítrico não influenciaram na adesão de células sanguíneas; a aplicação de PRP antes da deposição do tecido sanguíneo parece ter influenciado a adesão de células à superfície radicular; a utilização de EDTA e ácido cítrico em associação ao PRP favoreceram a adesão de células sanguíneas; o EDTA e o ácido cítrico removeram smear layer e expuseram túbulos dentinários, mas não foram eficazes na exposição de fibras colágenas.
Blood cell attachment to demineralized root surfaces of smoking patients
Keywords: Smear layer; Blood coagulation; Platelet-rich plasma; Camada de esfregaço; Coagulação sanguínea; Plasma rico em plaquetas